Estado da prática da engenharia de requisitos no desenvolvimento de aplicações móveis - (:unkn) unknown (Universidade Federal do Pampa, 2016)
The quantity of software applications related to mobile devices is in frantic progression, as well as the resources and the computer power offered by this kind of device. Though some “classic” techniques of software engineering can be transferred to this domain, these applications have to deal with a lot of limitations inherent to the mobile ecosystem that are not present in conventional desktop applications. One of the areas with the biggest importance, both in the traditional software engineering and on the one applied to mobile devices, is the Requirements Engineering. In this context, the general goal of this work is to identify the state of practice in requirements engineering used in the market for building mobile applications. To achieve this goal, a research was prepared and applied to mobile developers available on Google Play, obtaining 85 responses from 26 different countries. The results show that the time devoted to the Requirements Engineering is lower than recommended in the literature; less than half of survey participants performing the requirements inspection activity and few developers make use of approaches to modeling software requirements. Therefore, Requirements Engineering is neglected in many aspects by most mobile application developers. In this way, the academy should give greater emphasis to the study of Requirements Engineering, highlighting its importance for the development of quality software.
Keywords: Engenharia de software; Engenharia de Requisitos; Aplicações Móveis; Estado da Prática; Software Engineering; Requirements Engineering; Mobile Applications; State of Practice; CNPQ::CIENCIAS EXATAS E DA TERRA